Optimalisasi Kompetensi Literasi Numerasi Guru SD melalui Platform Pembelajaran Daring Menuju Sekolah yang di Cita-Citakan - Primasatya, Nurita; Nurfahrudhianto, Aan; Saidah, Karimatus; Permana, Erwin Putera; Kurnia, Ita; Daniswara, Naomi Diva; Putri, Veni Pratiwi Ananda (Universitas Nusantara PGRI Kediri, 2025)
This community service program aims to improve the numeracy literacy competency of elementary school teachers in Mojoroto District who are members of the Sekartaji Community. The existence of ANBK requires teachers to have competencies related to literacy and numeracy and the use of online learning platforms, so they can train students to solve problems related to numeracy literacy through online learning platforms. The methods used include socialization, training, technology implementation, mentoring and evaluation, and program sustainability. The results of this training showed that 63.6% of participants improved their understanding of literacy and numeracy. In addition, 89% of participants had good skills in developing teaching modules to teach literacy and numeracy through online learning platforms. The results of this training activity have an impact on teacher competency in designing learning, which will directly impact the quality of learning in the classroom.